-
Notifications
You must be signed in to change notification settings - Fork 0
/
Copy pathalgebraic_bounds.tex
258 lines (203 loc) · 20.3 KB
/
algebraic_bounds.tex
1
2
3
4
5
6
7
8
9
10
11
12
13
14
15
16
17
18
19
20
21
22
23
24
25
26
27
28
29
30
31
32
33
34
35
36
37
38
39
40
41
42
43
44
45
46
47
48
49
50
51
52
53
54
55
56
57
58
59
60
61
62
63
64
65
66
67
68
69
70
71
72
73
74
75
76
77
78
79
80
81
82
83
84
85
86
87
88
89
90
91
92
93
94
95
96
97
98
99
100
101
102
103
104
105
106
107
108
109
110
111
112
113
114
115
116
117
118
119
120
121
122
123
124
125
126
127
128
129
130
131
132
133
134
135
136
137
138
139
140
141
142
143
144
145
146
147
148
149
150
151
152
153
154
155
156
157
158
159
160
161
162
163
164
165
166
167
168
169
170
171
172
173
174
175
176
177
178
179
180
181
182
183
184
185
186
187
188
189
190
191
192
193
194
195
196
197
198
199
200
201
202
203
204
205
206
207
208
209
210
211
212
213
214
215
216
217
218
219
220
221
222
223
224
225
226
227
228
229
230
231
232
233
234
235
236
237
238
239
240
241
242
243
244
245
246
247
248
249
250
251
252
253
254
255
256
257
258
\documentclass[10pt,a4paper]{article}
\usepackage[utf8]{inputenc}
\usepackage[T1]{fontenc}
\usepackage{amsmath}
\usepackage{amsfonts}
\usepackage{amssymb}
\usepackage{graphicx}
\usepackage{amsthm}
\newtheorem{theorem}{Theorem}
%\newtheorem{proof}{Proof}
%% Author Preamble
\usepackage{todonotes}
\newcommand{\f}[1]{\mathfrak{#1}}
\usepackage[capitalize]{cleveref}
\usepackage{bm}
%\usepackage[style=numeric, backend=biber]{biblatex}
%\addbibresource{thesis.bib}
%% ~Author Preamble
\begin{document}
\todo[color=green, inline]{Fixed issue with using incorrect binomial coefficient}
\section{Algebraic GCD Bounds}
Having derived the probability that the GCD of products of randomly chosen positive integers is $B$-smooth, we now find more convenient bounds for this product representation.
\begin{theorem} The probability that $\gcd(\prod_{j=1}^n \f{a}_{1j}, ..., \prod_{j=1}^{n}\f{a}_{mj})$ is $B$-smooth is bounded above by
$$\frac{1}{\zeta_\mathcal{O}(m)}\prod_{\f{N}(\f{p})\leq B}\Big(1-\frac{1}{\f{N}(\f{p})^m}\Big)^{-1},$$
and is bounded below by
$$\prod_{B<\f{N}(\f{p})\leq\hat{n}} \Big[1 - \Big(1 - \Big(1 - \frac{1}{\f{N}(\f{p})}\Big)^n \Big)^m\Big] \cdot \prod_{\hat{n}<\f{N}(\f{p})\leq\hat{r}} \Big(1 - \Big(\frac{n}{\f{N}(\f{p})}\Big)^m\Big) \cdot \frac{1}{\zeta_\mathcal{O}(s)},$$
where $\hat{n}=\max\{n,B\}$, $\hat{r}=\max\{\hat{n}, \lfloor n^{\frac{m}{m-1}}+1\rfloor\}$, and $s = m(1 - \log_{\hat{r}}{n}) > 1$.
\end{theorem}
\noindent \textbf{Remark:} It is understood that for the lower bound, the first finite product is equal to 1 if $B = \hat{n}$, and the second finite product is equal to 1 if $\hat{n}=\hat{r}$.
\begin{proof}
We start by deriving the upper bound. Since $(1 - \frac{1}{\f{N}(\f{p})})^n$ decreases as a function of $n$ due to $1 - \frac{1}{\f{N}(\f{p})} \in (0, 1)$, we obtain
$$\prod_{B<\f{N}(\f{p})\leq\hat{n}} \Big[1 - \Big(1 - \Big(1 - \frac{1}{\f{N}(\f{p})}\Big)^n \Big)^m \Big] \leq \prod_{\f{N}(\f{p})>B} \Big(1 - \frac{1}{\f{N}(\f{p})^m}\Big) = \frac{1}{\zeta_\mathcal{O}(m)} \prod_{\f{N}(\f{p})\leq B} \Big(1 - \frac{1}{\f{N}(\f{p})^m}\Big)^{-1},$$
where the rightmost equality uses the infinite product representation of the Dedekind zeta function.
\vspace{.1 in}
Next, we derive the lower bound for our probabilistic expression. We start by splitting the product at $\hat{n}$. Then we apply Bernoulli's inequality in the form $(1 - x)^n \geq 1 - x$ where $x \in [0, 1]$ and $n \geq 1$, where we take $x = \frac{1}{\f{N}(\f{p})}$ where $\f{p}$ is a prime ideal such that $\f{N}(\f{p}) > \hat{n}$. This yields
$$\prod_{B<\f{N}(\f{p})\leq\hat{n}} \Big[1 - \Big(1 - \Big(1 - \frac{1}{\f{N}(\f{p})}\Big)^n \Big)^m \Big] \geq \prod_{B<\f{N}(\f{p})\leq \hat{n}}\Big[1 - \Big(1 - \Big(1 - \frac{1}{\f{N}(\f{p})}\Big)^n \Big)^m \Big] \cdot \prod_{\f{N}(\f{p})>\hat{n}}\Big(1 - \Big(\frac{n}{\f{N}(\f{p})}\Big)^m\Big).$$
\vspace{.1 in}
It remains to find a lower bound for $\prod_{\f{N}(\f{p})>\hat{n}} (1 - (\frac{n}{\f{N}(\f{p})})^m)$. From using the definition of $s$, we see that $\f{N}(\f{p}) \geq \hat{r}$ is equivalent to $(\frac{n}{\f{N}(\f{p})})^m \leq \frac{1}{\f{N}(\f{p})^s}$. Using this fact in conjunction to the infinite product representation for the Dedekind zeta function, we obtain
\begin{align*} \prod_{\f{N}(\f{p})>\hat{n}}\Big(1 - \Big(\frac{n}{\f{N}(\f{p})}\Big)^m\Big) &= \prod_{\hat{n}< \f{N}(\f{p}) \leq \hat{r}}\Big(1 - \Big(\frac{n}{\f{N}(\f{p})}\Big)^m\Big) \cdot \prod_{\f{N}{(\f{p})}>\hat{r}}\Big(1 - \Big(\frac{n}{\f{N}(\f{p})}\Big)^m\Big)\\ &\geq \prod_{\hat{n}< \f{N}(\f{p}) \leq \hat{r}}\Big(1 - \Big(\frac{n}{\f{N}(\f{p})}\Big)^m\Big) \cdot \prod_{\f{N}(\f{p})>\hat{r}}\Big(1 - \frac{1}{\f{N}(\f{p})^s}\Big)\\ &\geq \prod_{\hat{n}< \f{N}(\f{p}) \leq \hat{r}}\Big(1 - \Big(\frac{n}{\f{N}(\f{p})}\Big)^m\Big) \cdot \frac{1}{\zeta_\mathcal{O}(s)}. \end{align*}
The claimed lower bound now directly follows.
\vspace{.1 in}
It remains to show that $s > 1$. To this end, observe that since $r=\lfloor n^{\frac{m}{m-1}}+1\rfloor$ and $\hat{r} = \max\{n, B, r\}$, we have $\hat{r} \geq r > n^{\frac{m}{m-1}}$. Hence, we conclude that $s = m(1 - \log_{\hat{r}}{n}) > 1$ as required.
\end{proof}
\section{Algebraic K-GCD Bounds}
Having derived the probability that the $k$-GCD of products of randomly chosen positive integers is $B$-smooth, we now find more convenient bounds for this product representation.\newline
The following simplification will be useful for the following proofs:
\begin{align*}
\Big(1-\frac{1}{\f{N}(\f{p})}\Big)^n\Big(1+\frac{{}_nH_1}{\f{N}(\f{p})}+\mathellipsis+\frac{{}_nH_{k-1}}{\f{N}(\f{p})^{k-1}}\Big) = \sum_{t=0}^{k-1}\binom{n-1}{t-1}\Big(1-\frac{1}{\f{N}(\f{p})}\Big)^n\Big(\frac{1}{\f{N}(\f{p})}\Big)^t.
\end{align*}
\begin{theorem} The probability that $\gcd(\prod_{j=1}^n \f{a}_{1j}, ..., \prod_{j=1}^{n}\f{a}_{mj})$ is $B$-smooth is bounded above by
$$\frac{1}{\zeta_\mathcal{O}(m)}\prod_{\f{N}(\f{p})\leq B}\Big(1-\frac{1}{\f{N}(\f{p})^m}\Big)^{-1},$$
and is bounded below by
$$\prod_{B<\f{N}(\f{p})\leq\hat{n}} \Big[1 - \Big(1 -\Big(1-\frac{1}{\f{N}(\f{p})}\Big)^n\Big(1+\frac{{}_nH_1}{\f{N}(\f{p})}+\mathellipsis+\frac{{}_nH_{k-1}}{\f{N}(\f{p})^{k-1}}\Big)\Big)^m\Big] \cdot \prod_{\hat{n}<\f{N}(\f{p})\leq\hat{r}} \Big(1 - \Big(\frac{n}{\f{N}(\f{p})}\Big)^m\Big) \cdot \frac{1}{\zeta_\mathcal{O}(s)},$$
where $\hat{n}=\max\{n,B\}$, $\hat{r}=\max\{\hat{n}, \lfloor n^{\frac{m}{m-1}}+1\rfloor\}$, and $s = m(1 - \log_{\hat{r}}{n}) > 1$.
\end{theorem}
\noindent \textbf{Remark:} It is understood that for the lower bound, the first finite product is equal to 1 if $B = \hat{n}$, and the second finite product is equal to 1 if $\hat{n}=\hat{r}$.
\newline
\begin{proof}
We start by deriving the upper bound.
From the binomial formula, for $x=(1-\frac{1}{\f{N}(\f{p}^r)})$, and $y=\frac{1}{\f{N}(\f{p}^r)}$,
$$\sum_{t=0}^{k-1}\binom{n}{t}\Big(1-\frac{1}{\f{N}(\f{p}^r)}\Big)^{n-t}\Big(\frac{1}{\f{N}(\f{p}^r)}\Big)^t=(x+y)^n.$$
Next, we substitute an identity for the binomial coefficient,
$$\sum_{t=0}^{k-1}\Big(\frac{n}{k}\Big)\binom{n-1}{t-1}\Big(1-\frac{1}{\f{N}(\f{p}^r)}\Big)^{n-t}\Big(\frac{1}{\f{N}(\f{p}^r)}\Big)^t=(x+y)^n.$$
Which implies,
$$\sum_{t=0}^{k-1}\binom{n-1}{t-1}\Big(1-\frac{1}{\f{N}(\f{p}^r)}\Big)^{n-t}\Big(\frac{1}{\f{N}(\f{p}^r)}\Big)^t=\Big((x+y)^n\Big(\sum_{t=0}^{k-1}\frac{k}{n}\Big)\Big).$$
Substituting in $x,y$, for $k\leq n$, we see that
$$\sum_{t=0}^{k-1}\binom{n-1}{t-1}\Big(1-\frac{1}{\f{N}(\f{p}^r)}\Big)^{n-t}\Big(\frac{1}{\f{N}(\f{p}^r)}\Big)^t=\Big((x+y)^n\Big(\sum_{t=0}^{k-1}\frac{k}{n}\Big)\Big)\leq1.$$
Finally, by dividing by $\sum_{t=0}^{k-1}\Big(1-\frac{1}{\f{N}(\f{p}^r)}\Big)^{-t}$,
$$\sum_{t=0}^{k-1}\binom{n-1}{t-1}\Big(1-\frac{1}{\f{N}(\f{p}^r)}\Big)^{n}\Big(\frac{1}{\f{N}(\f{p}^r)}\Big)^t<\sum_{t=0}^{k-1}\Big(1-\frac{1}{\f{N}(\f{p}^r)}\Big)^t.$$
Thus we can form the following chain of inequalities,
\begin{align*}
&\prod_{B<\f{N}(\f{p})\leq\hat{n}} \Big[1 - \Big(1 -\Big(1-\frac{1}{\f{N}(\f{p})}\Big)^n\Big(1+\frac{{}_nH_1}{\f{N}(\f{p})}+\mathellipsis+\frac{{}_nH_{k-1}}{\f{N}(\f{p})^{k-1}}\Big)\Big)^m\Big] = \\
&\prod_{B<\f{N}(\f{p})\leq\hat{n}} \Big(1 -\Big(1-\frac{1}{\f{N}(\f{p})}\Big)^n\Big(1+\frac{{}_nH_1}{\f{N}(\f{p})}+\mathellipsis+\frac{{}_nH_{k-1}}{\f{N}(\f{p})^{k-1}}\Big)\Big)^m = \\
&\prod_{B<\f{N}(\f{p})\leq\hat{n}} \Big(1 - \sum_{t=0}^{k-1}\binom{n-1}{t-1}\Big(1-\frac{1}{\f{N}(\f{p})}\Big)^n\Big(\frac{1}{\f{N}(\f{p})}\Big)^t\Big)^m \leq \\
&\prod_{B<\f{N}(\f{p})\leq\hat{n}} \Big(1 - \sum_{t=0}^{k-1}\Big(1-\frac{1}{\f{N}(\f{p})}\Big)^t\Big)^m \leq \\
&\prod_{B<\f{N}(\f{p})\leq\hat{n}} \Big(1 - \Big(1-\frac{1}{\f{N}(\f{p})}\Big)\Big)^m \leq \\
&\prod_{B<\f{N}(\f{p})\leq\hat{n}} \Big(1-\frac{1}{\f{N}(\f{p})}\Big)^m \leq \\
&\prod_{B<\f{N}(\f{p})\leq\hat{n}} \Big(1-\frac{1}{\f{N}(\f{p})^m}\Big). \\
\end{align*}
Thus we have,
\begin{align*}
&\prod_{\f{N}(\f{p})>B} \Big[1 - \Big(1 -\Big(1-\frac{1}{\f{N}(\f{p})}\Big)^n\Big(1+\frac{{}_nH_1}{\f{N}(\f{p})}+\mathellipsis+\frac{{}_nH_{k-1}}{\f{N}(\f{p})^{k-1}}\Big)\Big)^m\Big] \leq \\
&\prod_{\f{N}(\f{p})>B} \Big(1 - \frac{1}{\f{N}(\f{p})^m}\Big) = \frac{1}{\zeta_\mathcal{O}(m)} \prod_{\f{N}(\f{p})\leq B} \Big(1 - \frac{1}{\f{N}(\f{p})^m}\Big)^{-1},
\end{align*}
where the rightmost equality uses the infinite product representation of the Dedekind zeta function.
\vspace{.1 in}
Next, we derive the lower bound for our probabilistic expression. First we split the product at $\hat{n}$,
\begin{align*}
&\prod_{B<\f{N}(\f{p})\leq\hat{n}} \Big[1 - \Big(1 -\Big(1-\frac{1}{\f{N}(\f{p})}\Big)^n\Big(1+\frac{{}_nH_1}{\f{N}(\f{p})}+\mathellipsis+\frac{{}_nH_{k-1}}{\f{N}(\f{p})^{k-1}}\Big)\Big)^m\Big]\\
&=\prod_{B<\f{N}(\f{p})\leq\hat{n}} \Big[1 - \Big(1 -\Big(1-\frac{1}{\f{N}(\f{p})}\Big)^n\Big(1+\frac{{}_nH_1}{\f{N}(\f{p})}+\mathellipsis+\frac{{}_nH_{k-1}}{\f{N}(\f{p})^{k-1}}\Big)\Big)^m\Big]\\
&\cdot\prod_{\f{N}(\f{p})\geq\hat{n}} \Big[1 - \Big(1 -\Big(1-\frac{1}{\f{N}(\f{p})}\Big)^n\Big(1+\frac{{}_nH_1}{\f{N}(\f{p})}+\mathellipsis+\frac{{}_nH_{k-1}}{\f{N}(\f{p})^{k-1}}\Big)\Big)^m\Big].\\
\end{align*}
Next, we apply our simplification to the right most product,
\begin{align*}
&\prod_{B<\f{N}(\f{p})\leq\hat{n}} \Big[1 - \Big(1 -\Big(1-\frac{1}{\f{N}(\f{p})}\Big)^n\Big(1+\frac{{}_nH_1}{\f{N}(\f{p})}+\mathellipsis+\frac{{}_nH_{k-1}}{\f{N}(\f{p})^{k-1}}\Big)\Big)^m\Big]\\
&\cdot\prod_{\f{N}(\f{p})\geq\hat{n}} \Big[1 - \Big(1 -\Big(1-\frac{1}{\f{N}(\f{p})}\Big)^n\Big(1+\frac{{}_nH_1}{\f{N}(\f{p})}+\mathellipsis+\frac{{}_nH_{k-1}}{\f{N}(\f{p})^{k-1}}\Big)\Big)^m\Big]\\
&=\prod_{B<\f{N}(\f{p})\leq\hat{n}} \Big[1 - \Big(1 -\Big(1-\frac{1}{\f{N}(\f{p})}\Big)^n\Big(1+\frac{{}_nH_1}{\f{N}(\f{p})}+\mathellipsis+\frac{{}_nH_{k-1}}{\f{N}(\f{p})^{k-1}}\Big)\Big)^m\Big]\\
&\cdot\prod_{\f{N}(\f{p})\geq\hat{n}} \Big[1 - \Big(1 -\sum_{t=0}^{k-1}\binom{n-1}{t-1}\Big(1-\frac{1}{\f{N}(\f{p})}\Big)^n\Big(\frac{1}{\f{N}(\f{p})}\Big)^t\Big)^m\Big].
\end{align*}
Next, using an estimate from Ryan DeMoss, we bound the summation in the rightmost product by applying Bernoulli's inequality in the form $(1 - x)^n \geq 1 - nx$ where $x \in [0, 1]$ and $n \geq 1$, where we take $x = \frac{1}{\f{N}(\f{p})}$ where $\f{p}$ is a prime ideal such that $\f{N}(\f{p}) > \hat{n}$. Thus for all $k\geq2$,
\begin{align*}
&\sum_{t=0}^{k-1}\binom{n-1}{t-1}\Big(1-\frac{1}{\f{N}(\f{p})}\Big)^n\Big(\frac{1}{\f{N}(\f{p})^t}\Big)\\ &\geq \Big(1-\frac{1}{\f{N}(\f{p})}\Big)\\
&\geq\Big(1-\frac{1}{\f{N}(\f{p})}\Big)^n+n\Big(1-\frac{1}{\f{N}(\f{p})}\Big)^{n-1}\Big(\frac{1}{\f{N}(\f{p})}\Big)\\
&=\Big(1-\frac{1}{\f{N}(\f{p})}\Big)^{n-1}\Big(1+\frac{n-1}{\f{N}(\f{p})}\Big)\\
&\geq\Big(1-\frac{n-1}{\f{N}(\f{p})}\Big)\Big(1+\frac{n-1}{\f{N}(\f{p})}\Big) \text{ by Bernoulli's inequality}\\
&=1-\Big(\frac{n-1}{\f{N}(\f{p})}\Big)^2\\
&\geq 1-\Big(\frac{n-1}{\f{N}(\f{p})}\Big)\\
&\geq 1-\Big(\frac{n}{\f{N}(\f{p})}\Big).\\
\end{align*}
Thus we have,
\begin{align*}
&\prod_{B<\f{N}(\f{p})\leq\hat{n}} \Big[1 - \Big(1 -\Big(1-\frac{1}{\f{N}(\f{p})}\Big)^n\Big(1+\frac{{}_nH_1}{\f{N}(\f{p})}+\mathellipsis+\frac{{}_nH_{k-1}}{\f{N}(\f{p})^{k-1}}\Big)\Big)^m\Big]\\
&\cdot\prod_{\f{N}(\f{p})\geq\hat{n}} \Big[1 - \Big(1 -\Big(1-\frac{1}{\f{N}(\f{p})}\Big)^n\Big(1+\frac{{}_nH_1}{\f{N}(\f{p})}+\mathellipsis+\frac{{}_nH_{k-1}}{\f{N}(\f{p})^{k-1}}\Big)\Big)^m\Big]\\
&\leq\prod_{B<\f{N}(\f{p})\leq\hat{n}} \Big[1 - \Big(1 -\Big(1-\frac{1}{\f{N}(\f{p})}\Big)^n\Big(1+\frac{{}_nH_1}{\f{N}(\f{p})}+\mathellipsis+\frac{{}_nH_{k-1}}{\f{N}(\f{p})^{k-1}}\Big)\Big)^m\Big]\cdot \prod_{\f{N}(\f{p})\geq\hat{n}} \Big(1 - \Big(\frac{n}{\f{N}(\f{p})}\Big)^m\Big).\\
\end{align*}
\vspace{.1 in}
It remains to find a lower bound for $\prod_{\f{N}(\f{p})>\hat{n}} (1 - (\frac{n}{\f{N}(\f{p})})^m)$. From using the definition of $s$, we see that $\f{N}(\f{p}) \geq \hat{r}$ is equivalent to $(\frac{n}{\f{N}(\f{p})})^m \leq \frac{1}{\f{N}(\f{p})^s}$. Using this fact in conjunction to the infinite product representation for the Dedekind zeta function, we obtain
\begin{align*} \prod_{\f{N}(\f{p})>\hat{n}}\Big(1 - \Big(\frac{n}{\f{N}(\f{p})}\Big)^m\Big) &= \prod_{\hat{n}< \f{N}(\f{p}) \leq \hat{r}}\Big(1 - \Big(\frac{n}{\f{N}(\f{p})}\Big)^m\Big) \cdot \prod_{\f{N}{(\f{p})}>\hat{r}}\Big(1 - \Big(\frac{n}{\f{N}(\f{p})}\Big)^m\Big)\\ &\geq \prod_{\hat{n}< \f{N}(\f{p}) \leq \hat{r}}\Big(1 - \Big(\frac{n}{\f{N}(\f{p})}\Big)^m\Big) \cdot \prod_{\f{N}(\f{p})>\hat{r}}\Big(1 - \frac{1}{\f{N}(\f{p})^s}\Big)\\ &\geq \prod_{\hat{n}< \f{N}(\f{p}) \leq \hat{r}}\Big(1 - \Big(\frac{n}{\f{N}(\f{p})}\Big)^m\Big) \cdot \frac{1}{\zeta_\mathcal{O}(s)}. \end{align*}
The claimed lower bound now directly follows.
\vspace{.1 in}
It remains to show that $s > 1$. To this end, observe that since $r=\lfloor n^{\frac{m}{m-1}}+1\rfloor$ and $\hat{r} = \max\{n, B, r\}$, we have $\hat{r} \geq r > n^{\frac{m}{m-1}}$. Hence, we conclude that $s = m(1 - \log_{\hat{r}}{n}) > 1$ as required.
\end{proof}
\section{Rational K-GCD Bounds}
Having derived the probability that the $k$-GCD of products of randomly chosen positive integers is $B$-smooth, we now find more convenient bounds for this product representation.\newline
The following simplification will be useful for the following proofs:
\begin{align*}
\Big(1-\frac{1}{p}\Big)^n\Big(1+\frac{{}_nH_1}{p}+\mathellipsis+\frac{{}_nH_{k-1}}{p^{k-1}}\Big) = \sum_{t=0}^{k-1}\binom{n-1}{t-1}\Big(1-\frac{1}{p}\Big)^n\Big(\frac{1}{{p}}\Big)^t.
\end{align*}
\begin{theorem} The probability that $\gcd(\prod_{j=1}^n r_{1j}, ..., \prod_{j=1}^{n}r_{mj})$ is $B$-smooth is bounded above by
$$\frac{1}{\zeta(m)}\prod_{p\leq B}\Big(1-\frac{1}{p^m}\Big)^{-1},$$
and is bounded below by
$$\prod_{B<p\leq\hat{n}} \Big[1 - \Big(1 -\Big(1-\frac{1}{p}\Big)^n\Big(1+\frac{{}_nH_1}{p}+\mathellipsis+\frac{{}_nH_{k-1}}{p^{k-1}}\Big)\Big)^m\Big] \cdot \prod_{\hat{n}<p\leq\hat{r}} \Big(1 - \Big(\frac{n}{p}\Big)^m\Big) \cdot \frac{1}{\zeta(s)},$$
where $\hat{n}=\max\{n,B\}$, $\hat{r}=\max\{\hat{n}, \lfloor n^{\frac{m}{m-1}}+1\rfloor\}$, and $s = m(1 - \log_{\hat{r}}{n}) > 1$.
\end{theorem}
\noindent \textbf{Remark:} It is understood that for the lower bound, the first finite product is equal to 1 if $B = \hat{n}$, and the second finite product is equal to 1 if $\hat{n}=\hat{r}$.
\newline
\begin{proof}
We start by deriving the upper bound.
From the binomial formula, for $x=(1-\frac{1}{p^r})$, and $y=\frac{1}{p^r}$,
$$\sum_{t=0}^{k-1}\binom{n}{t}\Big(1-\frac{1}{p^r}\Big)^{n-t}\Big(\frac{1}{p^r}\Big)^t=(x+y)^n.$$
Next, we substitute an identity for the binomial coefficient,
$$\sum_{t=0}^{k-1}\Big(\frac{n}{k}\Big)\binom{n-1}{t-1}\Big(1-\frac{1}{p^r}\Big)^{n-t}\Big(\frac{1}{p^r}\Big)^t=(x+y)^n.$$
Which implies,
$$\sum_{t=0}^{k-1}\binom{n-1}{t-1}\Big(1-\frac{1}{p^r}\Big)^{n-t}\Big(\frac{1}{p^r}\Big)^t=\Big((x+y)^n\Big(\sum_{t=0}^{k-1}\frac{k}{n}\Big)\Big).$$
Substituting in $x,y$, for $k\leq n$, we see that
$$\sum_{t=0}^{k-1}\binom{n-1}{t-1}\Big(1-\frac{1}{p^r}\Big)^{n-t}\Big(\frac{1}{p^r}\Big)^t=\Big((x+y)^n\Big(\sum_{t=0}^{k-1}\frac{k}{n}\Big)\Big)\leq1.$$
Finally, by dividing by $\sum_{t=0}^{k-1}\Big(1-\frac{1}{p^r}\Big)^{-t}$,
$$\sum_{t=0}^{k-1}\binom{n-1}{t-1}\Big(1-\frac{1}{p^r}\Big)^{n}\Big(\frac{1}{p^r}\Big)^t<\sum_{t=0}^{k-1}\Big(1-\frac{1}{p^r}\Big)^t.$$
Thus we can form the following chain of inequalities,
\begin{align*}
&\prod_{B<p\leq\hat{n}} \Big[1 - \Big(1 -\Big(1-\frac{1}{p}\Big)^n\Big(1+\frac{{}_nH_1}{p}+\mathellipsis+\frac{{}_nH_{k-1}}{p^{k-1}}\Big)\Big)^m\Big] = \\
&\prod_{B<p\leq\hat{n}} \Big(1 -\Big(1-\frac{1}{p}\Big)^n\Big(1+\frac{{}_nH_1}{p}+\mathellipsis+\frac{{}_nH_{k-1}}{p^{k-1}}\Big)\Big)^m = \\
&\prod_{B<p\leq\hat{n}} \Big(1 - \sum_{t=0}^{k-1}\binom{n-1}{t-1}\Big(1-\frac{1}{p}\Big)^n\Big(\frac{1}{p}\Big)^t\Big)^m \leq \\
&\prod_{B<p\leq\hat{n}} \Big(1 - \sum_{t=0}^{k-1}\Big(1-\frac{1}{p}\Big)^t\Big)^m \leq \\
&\prod_{B<p\leq\hat{n}} \Big(1 - \Big(1-\frac{1}{p}\Big)\Big)^m \leq \\
&\prod_{B<p\leq\hat{n}} \Big(1-\frac{1}{p}\Big)^m \leq \\
&\prod_{B<p\leq\hat{n}} \Big(1-\frac{1}{p^m}\Big). \\
\end{align*}
Thus we have,
\begin{align*}
&\prod_{p>B} \Big[1 - \Big(1 -\Big(1-\frac{1}{p}\Big)^n\Big(1+\frac{{}_nH_1}{p}+\mathellipsis+\frac{{}_nH_{k-1}}{p^{k-1}}\Big)\Big)^m\Big] \leq \\
&\prod_{p>B} \Big(1 - \frac{1}{p^m}\Big) = \frac{1}{\zeta(m)} \prod_{p\leq B} \Big(1 - \frac{1}{p^m}\Big)^{-1},
\end{align*}
where the rightmost equality uses the infinite product representation of the Riemann zeta function.
\vspace{.1 in}
Next, we derive the lower bound for our probabilistic expression. First we split the product at $\hat{n}$,
\begin{align*}
&\prod_{B<p\leq\hat{n}} \Big[1 - \Big(1 -\Big(1-\frac{1}{p}\Big)^n\Big(1+\frac{{}_nH_1}{p}+\mathellipsis+\frac{{}_nH_{k-1}}{p^{k-1}}\Big)\Big)^m\Big]\\
&=\prod_{B<p\leq\hat{n}} \Big[1 - \Big(1 -\Big(1-\frac{1}{p}\Big)^n\Big(1+\frac{{}_nH_1}{p}+\mathellipsis+\frac{{}_nH_{k-1}}{p^{k-1}}\Big)\Big)^m\Big]\\
&\cdot\prod_{p\geq\hat{n}} \Big[1 - \Big(1 -\Big(1-\frac{1}{p}\Big)^n\Big(1+\frac{{}_nH_1}{p}+\mathellipsis+\frac{{}_nH_{k-1}}{p^{k-1}}\Big)\Big)^m\Big].\\
\end{align*}
Next, we apply our simplification to the right most product,
\begin{align*}
&\prod_{B<p\leq\hat{n}} \Big[1 - \Big(1 -\Big(1-\frac{1}{p}\Big)^n\Big(1+\frac{{}_nH_1}{p}+\mathellipsis+\frac{{}_nH_{k-1}}{p^{k-1}}\Big)\Big)^m\Big]\\
&\cdot\prod_{p\geq\hat{n}} \Big[1 - \Big(1 -\Big(1-\frac{1}{p}\Big)^n\Big(1+\frac{{}_nH_1}{p}+\mathellipsis+\frac{{}_nH_{k-1}}{p^{k-1}}\Big)\Big)^m\Big]\\
&=\prod_{B<p\leq\hat{n}} \Big[1 - \Big(1 -\Big(1-\frac{1}{p}\Big)^n\Big(1+\frac{{}_nH_1}{p}+\mathellipsis+\frac{{}_nH_{k-1}}{p^{k-1}}\Big)\Big)^m\Big]\\
&\cdot\prod_{p\geq\hat{n}} \Big[1 - \Big(1 -\sum_{t=0}^{k-1}\binom{n-1}{t-1}\Big(1-\frac{1}{p}\Big)^n\Big(\frac{1}{p}\Big)^t\Big)^m\Big].
\end{align*}
Next, using an estimate from Ryan DeMoss, we bound the summation in the rightmost product by applying Bernoulli's inequality in the form $(1 - x)^n \geq 1 - nx$ where $x \in [0, 1]$ and $n \geq 1$, where we take $x = \frac{1}{p}$ where $p$ is a rational prime such that $p > \hat{n}$. Thus for all $k\geq2$,
\begin{align*}
&\sum_{t=0}^{k-1}\binom{n-1}{t-1}\Big(1-\frac{1}{p}\Big)^n\Big(\frac{1}{p}\Big)^t\\
&\geq \Big(1-\frac{1}{p}\Big)\\
&\geq\Big(1-\frac{1}{p}\Big)^n+n\Big(1-\frac{1}{p}\Big)^{n-1}\Big(\frac{1}{p}\Big)\\
&=\Big(1-\frac{1}{p}\Big)^{n-1}\Big(1+\frac{n-1}{p}\Big)\\
&\geq\Big(1-\frac{n-1}{p}\Big)\Big(1+\frac{n-1}{p}\Big) \text{ by Bernoulli's inequality}\\
&=1-\Big(\frac{n-1}{p}\Big)^2\\
&\geq 1-\Big(\frac{n-1}{p}\Big)\\
&\geq 1-\Big(\frac{n}{p}\Big).\\
\end{align*}
Thus we have,
\begin{align*}
&\prod_{B<p\leq\hat{n}} \Big[1 - \Big(1 -\Big(1-\frac{1}{p}\Big)^n\Big(1+\frac{{}_nH_1}{p}+\mathellipsis+\frac{{}_nH_{k-1}}{p^{k-1}}\Big)\Big)^m\Big]\\
&\cdot\prod_{p\geq\hat{n}} \Big[1 - \Big(1 -\Big(1-\frac{1}{p}\Big)^n\Big(1+\frac{{}_nH_1}{p}+\mathellipsis+\frac{{}_nH_{k-1}}{p^{k-1}}\Big)\Big)^m\Big]\\
&\leq\prod_{B<p\leq\hat{n}} \Big[1 - \Big(1 -\Big(1-\frac{1}{p}\Big)^n\Big(1+\frac{{}_nH_1}{p}+\mathellipsis+\frac{{}_nH_{k-1}}{p^{k-1}}\Big)\Big)^m\Big]\cdot \prod_{p\geq\hat{n}} \Big(1 - \Big(\frac{n}{p}\Big)^m\Big).\\
\end{align*}
\vspace{.1 in}
It remains to find a lower bound for $\prod_{p>\hat{n}} (1 - p^m)$. From using the definition of $s$, we see that $p \geq \hat{r}$ is equivalent to $(\frac{n}{p})^m \leq \frac{1}{p^s}$. Using this fact in conjunction to the infinite product representation for the Riemann zeta function, we obtain
\begin{align*} \prod_{p>\hat{n}}\Big(1 - \Big(\frac{n}{p}\Big)^m\Big) &= \prod_{\hat{n}< p \leq \hat{r}}\Big(1 - \Big(\frac{n}{p}\Big)^m\Big) \cdot \prod_{p>\hat{r}}\Big(1 - \Big(\frac{n}{p}\Big)^m\Big)\\ &\geq \prod_{\hat{n}< p \leq \hat{r}}\Big(1 - \Big(\frac{n}{p}\Big)^m\Big) \cdot \prod_{p>\hat{r}}\Big(1 - \frac{1}{p^s}\Big)\\ &\geq \prod_{\hat{n}< p \leq \hat{r}}\Big(1 - \Big(\frac{n}{p}\Big)^m\Big) \cdot \frac{1}{\zeta(s)}. \end{align*}
The claimed lower bound now directly follows.
\vspace{.1 in}
It remains to show that $s > 1$. To this end, observe that since $r=\lfloor n^{\frac{m}{m-1}}+1\rfloor$ and $\hat{r} = \max\{n, B, r\}$, we have $\hat{r} \geq r > n^{\frac{m}{m-1}}$. Hence, we conclude that $s = m(1 - \log_{\hat{r}}{n}) > 1$ as required.
\end{proof}
\end{document}